Konsep Diri Wanita Tuna Susila Dalam Novel Belenggu Karya Armijn Pane Berdasarkan Teori Interaksionisme Simbolik - Amini, Aisyah (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The novel Belenggu is considered to have received an award in the form of the best which was published during the new poet era. This paper shows the self-concept of prostitutes in the novel Belenggu. The self-concept of a handful of prostitutes is a feeling of fear of accepting the public's perspective on themselves who are lacking due to experiences in the dark past that make them no longer optimal in living their lives. This research is based on the theory of symbolic interactionism which aims to recognize self-concept through social reactions in the form of a community paradigm in denying prostitutes. The research method uses descriptive qualitative. Based on the analysis of the Belenggu novel, it can be seen that Rohayah is experiencing social construction so that she is emotionally disturbed because she feels that she is always oppressed by society's stigma about her. The bitter experience he experienced as a Dutch nyai gave rise to a bad self-concept but he had to stay strong to pick up the happiness of his life. Regulating self-concept is not easy, especially when there is discrimination in society that considers prostitutes to be unworthy of respect.